A Jacobi-Ritz approach for FGP beams with arbitrary boundary conditions based on a higher-order shear deformation theory. (1st September 2020) - Qin, Bin; Zhong, Rui; Wang, Qingshan; Zhao, Xing
Abstract: Vibration analysis is conducted for functionally grade porous (FGP) beams with arbitrary boundary conditions based on a general formulation. On the basis of higher-order shear deformation theory, the multi-segment strategy is employed for the modeling, where the FGP beam is separated into several segments. The artificial spring technique is introduced to simulate the boundary and continuity conditions. The Jacobi orthogonal polynomials are used to express the admissible displacement functions. Both free and forced (steady-state and transient) vibration analyses are conducted for the FGP beams, where three types of porous distributions are considered. The convergence characteristics and correctness of the present method are presented through convergence and comparison studies. Parametric studies are conducted for the dynamic analysis of FGP beams, where the effects of porous distribution type, porous coefficient, boundary conditions (including both classic and elastic boundary conditions) and load pulses are investigated.